Noonan Syndrome with cleft palate: A rare case report - Munish Kumar; Vinod Vijay Chandar; Sridevi Koduri; Shailaja Sankireddy (Wolters Kluwer Medknow Publications, 2016)
Noonan syndrome is a clinically and genetically heterogeneous condition characterized by distinctive facial features, short stature, chest deformity, congenital heart diseases and other comorbidities. It is an autosomal dominant disorder with complete penetrance but variable expressivity. Until recently, diagnosis was based solely on clinical findings, however, genetic mutations responsible for Noonan syndrome, PTPN11 was identified on chromosome number 12 resulting in a gain of function of the nonreceptor protein tyrosine phosphatase SHP-2 protein in 61% of the patients with an estimated prevalence of 1 in 1000 to 1 in 2500 live births, which appears to be consistent worldwide. There are also evidences of autosomal recessive forms of Noonan syndrome. This is a case report of Noonan syndrome with a rare presentation of soft tissue cleft palate.